Budidaya Tanaman Karet untuk Perekonomian yang Lebih Positif - Latif, Adi Sofyana; Arslan, Rijal; Saga, Baharudin; Septanta, Rananda (Jurnal PKM Manajemen Bisnis, 2024)
Rubber plants are a type of medicinal plant that has many health benefits, including treating small wounds, as a medical device, preventing stomach acid, for clothing, treating body aches, and as a fever-reducing medicine. The purpose of this community service is to provide information on how to increase the potential of natural resources located in Lebak, which is an area that has quite high potential in the rubber plantation business in general, but currently it has not been utilized optimally by the local community at this time. Most of the rubber plants that are produced are sold individually without knowing the harvest that the accounting information system consumes. This is due to a lack of innovation from the local community. Therefore, cultivating rubber plants is one way that can be done by harvesting quite small or large areas of land that can be put to good use, maintaining nutritional value and increasing economic value. With this cultivation empowerment, it is hoped that it can help improve the economy of the Lebak community and take advantage of the harvest of rubber plants for social welfare which is more durable to give rise to various innovations in processing rubber itself in a sustainable manner.